2018
DOI: 10.1140/epjc/s10052-018-6220-3
|View full text |Cite
|
Sign up to set email alerts
|

Weak decays of doubly heavy charm $$\Omega _{cc}^{+}$$ Ω cc + baryon

Abstract: We investigate the two-body non-leptonic decays of doubly charm strange, + cc , baryon. The branching ratios of the + cc baryon decays involving a pseudoscalar meson for CKM-favored and-suppressed modes are determined by employing the pole model and the factorization hypothesis. We give the first estimates of the non-factorizable Wexchange contributions of + cc decay in the pole model. We find that the branching ratios of some decays receive contributions, exclusively from the W-exchange diagrams, are as large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 97 publications
1
21
0
Order By: Relevance
“…F(0), m f it and δ correspond to the three fitting parameters in Eq. (30) or (31). The results without asterisks are obtained by fitting the form factors with Eq.…”
Section: Transition Form Factorsmentioning
confidence: 99%
“…F(0), m f it and δ correspond to the three fitting parameters in Eq. (30) or (31). The results without asterisks are obtained by fitting the form factors with Eq.…”
Section: Transition Form Factorsmentioning
confidence: 99%
“…In Table 11, we compare our rate results with the results of some other approaches [37][38][39][40][41][42]. All calculations approximately agree on the rate of the decay Ξ ++ cc → Ξ + c + ρ + , which is predicted to have a large branching ratio of ∼ 16 %.…”
Section: Numerical Resultsmentioning
confidence: 60%
“…Width (in 10 −13 GeV) GIKLT [22,43] DS [37,39] JHL [38] WYZ [40] YJLLWZ [41] KL [42] Ξ The only free parameter in our approach is the size parameter Λ cc of the double heavy baryons, for which we have chosen Λ cc = 0.8675 GeV in Tables 7-10. In order to estimate the uncertainty caused by the choice of the size parameter, we allow the size parameter to vary from 0.6 to 1.135 GeV.…”
Section: Modementioning
confidence: 99%
“…Width (in 10 −13 GeV) GIKLT [31,32] DS [18,19] into account W-exchange contributions. One can see from our analysis that the W-exchange contributions are generally not suppressed.…”
Section: Modementioning
confidence: 99%
“…In Ref. [19] the same approach has been applied to the nonleptonic decay modes of the double charm strange Ω + cc baryon. It was found that the branching ratios of some of the nonleptonic Ω + cc decay modes obtain contributions solely from W-exchange diagrams, resulting in branching ratios as large as ∼ O(10 −2 ).…”
Section: Introductionmentioning
confidence: 99%